Clinical-Radiological Patterns and Histopathological Outcomes in Non-Thyroid Extraocular Muscle Enlargement: Retrospective Case Series and Current Concepts. Issue 3 (May 2020) - Savino, Gustavo; Midena, Giulia; Tartaglione, Tommaso; Milonia, Luca; Caputo, Carmela Grazia; Grimaldi, Gabriela
Abstract : Purpose: To report a single-center experience with non-thyroid causes of extraocular muscle enlargement (EME), describing the association between clinical-radiological findings at presentation and the final histopathological diagnosis. Methods: Retrospective consecutive case series of 59 patients with single or multiple EME on orbital imaging, in the absence of an etiological diagnosis at the time of presentation. All patients were submitted to orbital muscle biopsy in order to achieve a final etiological diagnosis. Patients with a confirmed diagnosis of thyroid-associated orbitopathy and vascular causes of EME which were angiographically and clinically diagnosed were excluded. Orbital ultrasound and radiologic evaluation (CT and/or MRI) were performed before surgery in all cases. Main outcomes measured included initial clinical-radiological findings and final histopathological features of EME. Results: A diagnosis of lymphoma was confirmed in 13 cases (22%). Sixteen cases (27%) were diagnosed as orbital inflammatory disease including nonspecific idiopathic orbital inflammatory disease in 9 cases, IgG4-related disease in 4 cases, and sclerosing idiopathic orbital inflammatory disease in 3 cases. In 11 patients (18%), a diagnosis of metastatic tumor was made, whereas sarcoidosis, vascular malformations, Erdheim-Chester, and necrobiotic xanthogranuloma were diagnosed in 8 eyes (13.5%). Three patients (5%) with single muscle enlargement developed Graves disease 10 months later. Four patients (6.7%) were diagnosed with granulomatosis with polyangiitis. In 2 cases (3.3%), the diagnosis was unknown, with inconclusive biopsy results. Differential patterns for inflammatory/vascular, lymphomatous and metastatic EME were identified based on age and gender distribution and clinical-radiological characteristics at presentation. Conclusions: Initial clinical and radiological features may orientate the differential diagnosis of non-thyroid EME. Abstract : Clinical-radiological patterns of non-thyroid extraocular muscle enlargement can be identified, possibly orientating the differential diagnosis.